Baculovirus capsid display in vaccination schemes: effect of a previous immunity against the vector on the cytotoxic response to delivered antigens - Molinari, Maria Paula (2018)
The baculovirus Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) infects lepidopteran invertebrates as natural hosts, although it also has been used as display vector for vaccine development. In this work, we evaluated the effectiveness of repetitive doses of AcMNPV-based vectors on the cytotoxic immune response specific to the capsid-displayed heterologous antigen ovalbumin (OVA). Our results demonstrate that baculovirus vectors induce a boosting effect in the cytotoxic immune response to OVA, making possible to recover the levels obtained in the primary response. Moreover, mice preimmunized with wild-type baculovirus showed a complete lack of antigen-specific CD8 cytotoxic T lymphocytes (CTLs) that may be related to the presence of antibodies directed to baculoviral surface proteins, particularly to GP64. However, baculovirus was able to induce the innate immune response in spite of a previous response against this vector, although some quantitative differences reflect a distinct activation of the immune cells in prime and boost. This is the first report in which the novel capsid display strategy is evaluated in prime-boost schemes to improve efficient CTL responses.